Geodynamic Characteristics in the Southwest Margin of South China Sea - Yao, Yongjian; Zhang, Jian; Dong, Miao; Zhu, Rongwei; Xu, Zhiying; Yang, Xiaodong; Liu, Hailing (Frontiers in Earth Science, 2022)
The strike-slip fault system in the southwestern margin of South China Sea (SCS) lies on the transition zone between the continental shelf and slope of SCS, which is an important ocean–continent boundary. By using submarine heat flow data, a seismic shear wave tomography model, and gravity potential field data, this paper investigates the distribution of submarine heat flow in the southwestern margin of SCS, the thermal–rheological structure of the crust and mantle, the temperature–viscosity characteristics of the upper mantle Vs low-velocity layer, the tangential stress field of the rheological boundary layer at the lithosphere base, and the convective velocity structure of the mantle asthenosphere. Our new results show that the deep geothermal activity in the southwestern margin of SCS is intense, and the high heat flow area of the mantle with Qm/Qs >70% is distributed along an NNE-trending strip. Moreover, both the east and west sides of the strike–slip fault zone correspond to two low-value areas with a viscosity coefficient of 1021–1022 Pa⋅s at Moho depth, and beneath the Nansha Block are strong and cold blocks with a viscosity coefficient of 1024–1025 Pa⋅s. The northward and eastward shear stress components τN and τE of the rheological boundary layer at the base of the lithosphere mantle decrease with depth. At 65-km depth, both τN and τE are greater than 5.5 × 108 N/m2. At 100-km depth, both τN and τE are less than 1 × 108 N/m2. The calculation results based on the seismic shear wave model of the upper mantle and the gravimetric geoid model indicate that the depth of 120–250 km is the low-velocity layer, and the average temperature of the mantle at 180-km depth can be up to 1,300°C. Moreover, the average effective viscosity coefficient is close to 1018 Pa⋅s, which satisfies the temperature and viscosity conditions for partial melting or convective migration of mantle material. The mantle convection calculation results show that the average flow rate is 8.5 cm/a at 200-km depth and 2.2 cm/a at 400-km depth.